PELATIHAN TEKNIK FOTOGRAFI DAN VIDEO EDITING UNTUK MENINGKATKAN KEMAMPUAN MULTIMEDIA MAHASIWA FATONI UNIVERSITY THAILAND - Ibnu Siswanto; Beniati Lestyarini; Muhammad Irfan Luthfi; Islahuddin Islahuddin (As-Sidanah, 2024)
The target partners in this international collaboration community service program are Fatoni University students in Thailand. The majority of students are of Malay descent. Based on the communication that has been established between Fatoni University and Universitas Negeri Yogyakarta, it is known that Fatoni University students need photography and video editing training to improve their competence, especially in supporting tourism. Therefore, this international collaboration community service program was organizing an online photography and video editing training which involved 42 students from Fatoni University as participants and 20 students from Universitas Negeri Yogyakarta as peer students. Apart from introducing photography and video editing techniques, this program also introduces various cultures in Indonesia. What's more, the students participating in this program also interacted with each other so that they could add to their international exposure. Interaction between students is carried out through break-out rooms, which allow fellow participants and companions to communicate with each other and gain international experience. After participating in this training activity, participants from Fatoni University produced a photograph taken independently and were assessed by the community service implementing team. The result showed that the participants were satisfied with the program and obtained knowledge and skills in photography.